Introduction: Literacy ideologies. (July 2018) - Hasselbacher, Stephanie
Abstract: This special section explores contexts in which established ways of using written language have been retooled to support indigenous or "non-mainstream" ideologies of authority, including the incorporation of novel literacies into existing local language practices. This collection of papers addresses potential conflicts between historical and/or hegemonic literacy ideologies and novel literacy practices by illustrating ways in which authoritative semiotic modalities can be utilized to legitimize a form of literacy that was non-existent or has historically been positioned as inferior to standardized, hegemonic forms of writing. This introduction provides some relevant working definitions, points to common themes in the collection, and summarizes the ethnographic contexts explored by contributors to the special section. Highlights: A brief introduction to the special issue "Literacy Ideologies". Provides shared terminology and introduces relevant anthropological concepts, including seeming conflicts between scholarly and popular conceptions of literacy. Summarizes contributions to the special section.